Tetrahydroquinoline/4, 5‐Dihydroisoxazole Molecular Hybrids as Inhibitors of Breast Cancer Resistance Protein (BCRP/ABCG2). (18th May 2021) - Vesga, Luis C.; Kronenberger, Thales; Tonduru, Arun Kumar; Kita, Diogo Henrique; Zattoni, Ingrid Fatima; Bernal, Cristian Camilo; Bohórquez, Arnold R. Romero; Mendez‐Sánchez, Stelia Carolina; Ambudkar, Suresh V.; Valdameri, Glaucio; Poso, Antti
Abstract: Multidrug resistance (MDR) is one of the major factors in the failure of many chemotherapy approaches. In cancer cells, MDR is mainly associated with the expression of ABC transporters such as P‐glycoprotein, MRP1 and ABCG2. Despite major efforts to develop new selective and potent inhibitors of ABC drug transporters, no ABCG2‐specific inhibitors for clinical use are yet available. Here, we report the evaluation of sixteen tetrahydroquinoline/4, 5‐dihydroisoxazole derivatives as a new class of ABCG2 inhibitors. The affinity of the five best inhibitors was further investigated by the vanadate‐sensitive ATPase assay. Molecular modelling data, proposing a potential binding mode, suggest that they can inhibit the ABCG2 activity by binding on site S1, previously reported as inhibitors binding region, as well targeting site S2, a selective region for substrates, and by specifically interacting with residues Asn436, Gln398, and Leu555. Altogether, this study provided new insights into THQ/4, 5‐dihydroisoxazole molecular hybrids, generating great potential for the development of novel most potent ABCG2 inhibitors. Abstract : Tetrahydroquinoline/4, 5‐dihydroisoxazole hybrids can inhibit the ABCG2 transporter activity and increase the ATP hydrolysis in cells overexpressing ABCG2. Molecular docking and molecular dynamics simulation results suggest that molecular hybrids inhibit ABCG2 activity by binding at the inhibitor binding region, as well as the substrate binding regions.